Age and Growth of the Rio Grande Silvery Minnow, an Endangered, Short‐Lived Cyprinid of the North American Southwest. Issue 2 (25th March 2018) - Horwitz, Richard J.; Keller, David H.; Overbeck, Paul F.; Platania, Steven P.; Dudley, Robert K.; Carson, Evan W.
Abstract: This study provides the first comprehensive evaluation of age and age–length relationships from an extant population of the federally endangered Rio Grande Silvery Minnow Hybognathus amarus . The surveyed population was from three fragmented reaches within about 290 km of the middle Rio Grande in New Mexico, the last protected population in the historical range of the species. A total of 158 Rio Grande Silvery Minnows were collected in autumn 2009 ( n = 83) and spring 2010 ( n = 75), with sampling designed to fill six 10‐mm size‐class bins that represent the size range characteristic of the juvenile and adult population. Age was then determined directly for each specimen independently by two investigators, each using otoliths and scales; growth rates were estimated via back‐calculation of length at age from otoliths. The results confirm that individuals in the contemporary population are short‐lived, with very few surviving to their second or third summers. For historical comparison, the ages of a small collection of Rio Grande Silvery Minnows taken in August 1874 were evaluated using scales. The specimens in this historical collection ranged from age 0 to age 2, similar to the age range for the autumn 2009 collection and incongruent with a previously published report of five age‐classes (ages 1–5) for 13 of these specimens. Our results corroborate the age‐structure derived from temporal tracking of length frequency histograms generated under the Rio Grande Silvery Minnow Population Monitoring Project and validate current management of the species as short‐lived. Our age range and age–length relationships are also similar to those of other well‐studied Hybognathus spp., and the results from our study may aid management of these closely related, short‐lived pelagophil minnows. While additional research is needed to clarify the areas of age–length overlap, the crucial findings of this study should facilitate implementation of an appropriate management policy for this short‐lived, federally endangered cyprinid.